Hypoxia Impairs Initial Outgrowth of Endothelial Colony Forming Cells and Reduces Their Proliferative and Sprouting Potential - Tasev, Dimitar; Dekker-Vroling, Laura; van Wijhe, Michiel; Broxterman, Henk J.; Koolwijk, Pieter; van Hinsbergh, Victor W. M. (Frontiers in Medicine, 2018)
Vascular homeostasis and regeneration in ischemic tissue relies on intrinsic competence of the tissue to rapidly recruit endothelial cells for vascularization. The mononuclear cell (MNC) fraction of blood contains circulating progenitors committed to endothelial lineage. These progenitors give rise to endothelial colony-forming cells (ECFCs) that actively participate in neovascularization of ischemic tissue. To evaluate if the initial clonal outgrowth of ECFCs from cord (CB) and peripheral blood (PB) was stimulated by hypoxic conditions, MNCs obtained from CB and PB were subjected at 20% and 1% O2 cell culture conditions. Clonal outgrowth was followed during a 30 days incubation period. Hypoxia impaired the initial outgrowth of ECFC colonies from CB and also reduced their number that were developing from PB MNCs. Three days of oxygenation (20% O2) prior to hypoxia could overcome the initial CB-ECFC outgrowth. Once proliferating and subcultured the CB-ECFCs growth was only modestly affected by hypoxia (18±2% reduction); proliferation of PB-ECFCs was reduced to a similar extent. Early passages of subcultured CB- and PB-ECFCs contained only viable cells and few if any senescent cells, but the clonal ability of subcultured PB-ECFCs was reduced by 30% for PB-ECFCs. Tube formation by subcultured PB-ECFCs was also markedly inhibited by continuous exposure to 1% O2. Gene expression profiles point to regulation of the cell cycle and metabolism as major altered gene clusters. Finally we discuss our counterintuitive observations in the context of the important role that hypoxia has in promoting neovascularization.